‘Bring the whole tithe into the storehouse’: The tithe and sustainable development in Ghanaian Pentecostalism - Emmanuel A. Kenin (African Journal of Pentecostal Studies)
Background: This article explores the Church of Pentecost’s (CoP) theology of tithes and its intersection with sustainable development in Ghana. This research is grounded on the theory that the CoP through the Pentecost Social Services (PENTSOS) as well as other Church-initiated interventions, is pursuing sustainable development in Ghana through her theology of tithes.